Integration of Tumor Microenvironment in Patient-Derived Organoid Models Help Define Precision Medicine of Renal Cell Carcinoma - Wang, Bingran; Xue, Yizheng; Zhai, Wei (Frontiers in Immunology, 2022)
Renal cell carcinoma (RCC) is a common urological tumor, with poor prognosis, as the result of insensitivity to chemotherapy and radiotherapy. About 20-30% patients with RCC have metastasis at the first diagnosis, so that only systemic treatment is possible. Due to the heterogeneity of renal tumor, responses to drug differ from person to person. Consequently, patient derived organoid, highly recapitulating tumor heterogeneity, becomes a promising model for high throughput ex vivo drug screening and thus guide the drug choice of patient with renal cell carcinoma. Systemic treatment of RCC mainly targets tumor microenvironment, including neovasculature and immune cells. We reviewed several methods with which patient derived organoid models mimic the heterogeneity of not only tumor epithelium but also the tumor microenvironment. We further discuss some new aspects for the development of patient derived organoid, preserving in vivo conditions in patients with RCC.